Additive manufacturing method of solid waste-based brick mud structure composite material

Through 3D printing technology combining alkali-excited solid waste materials and furan resin, solid waste-based brick and mud structure composite materials were prepared, which solved the problem of insufficient toughness and impact resistance of existing concrete 3D printing materials, and achieved high-performance and low-cost brick and mud structure preparation.

CN119734341AActive Publication Date: 2025-04-01HEBEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510018304.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing concrete 3D printing materials and components have good compressive strength, but their toughness and impact resistance are poor, making it difficult to meet the high-performance requirements in the construction field.

Method used

3D printing technology is used to combine alkali-excited solid waste materials and thermosetting resin furan resin to prepare solid waste-based brick and mud structure composite materials through coordinated processes of paving molding and laser subtraction, achieving low-cost 3D printing and precise molding control of brick and mud structures.

Benefits of technology

It improves the overall degree and synergistic effect of the brick mud structure, enhances its compressive strength and toughness, reduces preparation costs, and is suitable for applications in large-scale industrial production and construction fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734341A_ABST
    Figure CN119734341A_ABST
Patent Text Reader

Abstract

The invention relates to an additive manufacturing method of a solid waste-based brick-mud structure composite material, which comprises the following steps: taking an alkali-activated solid waste material as a brick, and taking thermosetting furan resin as mud; the alkali-activated solid waste material is prepared from the following components in parts by weight: 80 to 85 parts of granite powder, 27.4 to 30 parts of slag, 5 to 8 parts of silica fume, 1.5 to 3 parts of fly ash, 0.41 to 0.43 part of basalt fiber with the length of 0.8 to 1.2 mm, 25 to 27 parts of water, 3.0 to 3.5 parts of sodium hydroxide and 6.0 to 7.0 parts of sodium silicate solution. The weight part ratio of the granite powder according to the grain composition is (100-120) mesh: 200 mesh = 1: (1-1.5), and the brick-mud structure composite material is prepared by adopting a paving type additive and laser subtractive synergistic process. Rolling is carried out after paving of the brick layer and the mud layer every time, pressurizing compaction in the printing process is achieved, bricks and mud are combined more tightly, the synergistic effect of the two materials is better, loss of the compressive strength of the brick-mud structure is effectively reduced, and the strength and toughness of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of 3D printing materials and printing technology, and in particular to an additive manufacturing method for a solid waste-based brick-mud structure composite material. Background Art

[0002] Concrete 3D printing technology is a new technology. As a new type of concrete formless forming technology, it can apply computer-aided design tools to the construction process. This technology has many advantages, such as fast production speed, economic efficiency, and relatively low cost, but the existing concrete 3D printing materials and components have good compressive strength, but poor toughness and impact resistance, which need to be improved. Brick-mud bionic structure has high toughness and good impact resistance, so brick-mud bionic structure can be used to improve the above problems.

[0003] Brick-mud bionic structures usually contain two or more different material phases, one of which (such as "brick") provides strength and rigidity, and the other (such as "mud") provides toughness and plasticity. The existing brick-mud bionic structure preparation process involves complex process steps, such as ice template-freeze drying method and bionic mineralization method. Some use laser cutting preparation method, which cuts brick shapes from existing ceramic sheets, then manually fills resin materials, and manually overlaps and presses the processed ceramic sheets to form, so as to achieve precise control of brick shapes and meet the preparation of large-scale brick-mud structural components. Although these methods can prepare "mud-brick" structures with fine structures, the process is complicated, the preparation is cumbersome, the cost is high, and it is difficult to meet the requirements of large-scale industrial production. In addition, the above methods are mainly used to prepare ceramic brick-mud structural materials, which are not suitable for the construction field and building materials. Therefore, it is necessary to combine 3D printing technology to prepare low-cost, high-performance brick-mud structural composite materials for building materials. Summary of the invention

[0004] The purpose of the present invention is to provide an additive manufacturing method for solid waste-based brick-mud structure composite materials, which adopts 3D printing technology to utilize paving molding additive and laser subtractive collaborative preparation, thereby solving the problem of complex preparation process in the background technology and difficulty in meeting large-scale industrial production, and realizing 3D printing and precise control of molding of alkali-activated solid waste material brick-mud structure, improving the synergy between brick-mud structures, and making the structure more compact.

[0005] To achieve the above object, the technical solution of the present invention is: An additive manufacturing method for a solid waste-based brick-mud structure composite material, using alkali-activated solid waste materials as bricks and thermosetting resin furan resin as mud; The alkali-activated solid waste material comprises, by weight, 80-85 parts of granite powder, 27.4-30 parts of slag, 5-8 parts of silica fume, 1.5-3 parts of fly ash, 0.41-0.43 parts of basalt fiber with a length of 0.8-1.2 mm, 25-27 parts of water, 3.0-3.5 parts of sodium hydroxide, and 6.0-7.0 parts of sodium silicate solution; The weight ratio of the granite powder according to the particle grading is 100-120 mesh: 200 mesh = 1: (1-1.5) The preparation process of the composite material is: 1) placing granite powder, slag, silica ash, fly ash and basalt fiber in a stirring pot and stirring them evenly to obtain a uniformly mixed dry material; placing the mixed dry material and water in a stirring pot and stirring them evenly to obtain a uniformly mixed wet material; quickly pouring sodium hydroxide tablets into a beaker containing sodium silicate solution and stirring them evenly to obtain an alkali activator; Putting the alkali activator and the mixed wet material into a stirring pot and stirring them evenly to obtain the alkali-activated solid waste material; 2) Printing is performed using a 3D printing device, which is equipped with a heating lamp, a fiber laser, a scraper and a roller, and the distance between the heating lamp and the workbench is 35-45 cm; after each layer of alkali-excited solid waste material is printed, the current layer is evenly spread using a scraper, and the fiber laser is used to cut the paved plane according to a set path. Except for the bottom layer, each layer of cutting completely penetrates the current layer, and the current layer is divided into bricks, and then irradiated with a 1500-1600W power heating lamp for 5-6 minutes, so that the current layer quickly hardens and reacts tightly; Furan resin is extruded on the alkali-activated solid waste material layer after being irradiated by a heat lamp, and spread by a scraper. After spreading, it is irradiated by a 1500-1600W power heat lamp for 4-5 minutes to form a resin material layer on the brick layer. When the resin is heated and solidified to a non-sticky roller, the roller is started to roll the layer, so that the resin material layer and the alkali-activated solid waste material layer are organically and tightly combined; The spreading, cutting, baking and rolling processes of the alkali-activated solid waste material and furan resin are repeated until the printing reaches the target height to obtain a brick-mud structure composite material.

[0006] The powder activity grade of the slag is S105, and the density is not less than 1.3g / cm 3 , CaO content is not less than 40%, SiO2 content is not less than 25%; The silica fume has a SiO2 content of not less than 80%; The sodium hydroxide is a solid tablet, analytically pure, with a content greater than 96% and a relative molecular mass of 40. The sodium silicate solution is SP38, with a solid content of 35.5, a Baume degree of 38.5, and a density of 1.366 kg / m 3 , pH value is 10.13, modulus is 3.26; The fly ash powder has a particle size of 1250 mesh and a density of 2.3 g / cm 3 , SiO2 content is not less than 55%, Al2O3 content is not less than 28%; The basalt fiber has a single filament diameter of 6.23 um, a breaking diameter of 1937 MPa, an elastic modulus of 79 Gpa, and a breaking elongation of 2.9.

[0007] Furthermore, the granite powder is ground from granite in Laizhou, Shandong, the granite compressive strength ranges from 100MPa to 200MPa, and the particle grading of the granite powder is 100-120 mesh: 200 mesh = 1:1 in terms of weight ratio.

[0008] Furthermore, the power of the baking lamp is 1500W, the distance from the workbench is 40cm, the irradiation time for the brick layer is 6 minutes, and the irradiation time for the mud layer is 5 minutes.

[0009] Furthermore, the thickness of the resin material layer is 0.2-0.5 mm, the rolling depth of the roller is 0.1 mm, and the rolling depth is the depth of the roller penetrating into the paving layer; the thickness of the brick layer printing layer is 1 mm.

[0010] Furthermore, the laser power of the fiber laser is 1000W, the laser energy during cutting is 45%, and the laser speed is 120mm / s.

[0011] The present invention also protects a solid waste-based brick-mud structure composite material obtained by the above-mentioned manufacturing method.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention realizes low-cost 3D printing preparation of brick-mud structures using alkali-activated solid waste materials, facilitating the application of brick-mud structures in the field of construction.

[0013] The present invention effectively avoids the gap defects caused by connecting strips when forming solid surfaces in other printing methods (SLA, SLS, 3DP, FDM, etc.) by spreading the surface, and improves the forming efficiency and its integrity compared to the plane composed of strips.

[0014] The present invention performs rolling after each paving of the "brick" layer and the "mud" layer. During the rolling process, the resin is in a semi-dry state and does not stick to the roller. The rolling process realizes pressurization and compaction during the printing process, so that the "brick" and the "mud" are more closely combined, and the synergistic effect of the two materials is better, which effectively reduces the loss of compressive strength of the brick-mud structure and improves the strength and toughness of the composite material.

[0015] The present invention realizes free design of brick shapes through laser cutting, and utilizes laser to completely penetrate the printed layer acting as the "brick" along the brick-shaped path, so that the resin material can bond the upper and lower layers more tightly through the through seams between the bricks, thereby enhancing various performances of the printed structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the process of the collaborative process of paving-type additive and laser subtractive in the present invention.

[0017] Figure 2 It is a structural schematic diagram of the 3D printing device of the present invention.

[0018] Figure 3 A schematic diagram of a brick type of a brick-and-mud structure according to an embodiment of the present invention.

[0019] Figure 4 This is a schematic diagram of the stacking of layers of a brick and mud structure according to an embodiment of the present invention.

[0020] The markings in the figure are: 1. Left material tank; 2. Right material tank; 3. Waste bin; 4. Scraper; 5. Roller; 6. Feed pipe; 7. Baking lamp; 8. Vibrating mirror; 9. Fiber laser; 10. Extrusion head; 11. Workbench; 12. Machine casing; 13. Furan resin acting as "mud"; 14. Alkali-activated solid waste material acting as "brick". DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention.

[0022] The present invention is based on a solid waste-based brick-mud structure composite material in the construction field, which includes an alkali-activated solid waste material that acts as a "brick" and a thermosetting resin furan resin that acts as a "mud". The alkali-activated solid waste material is made using the alkali activation principle, including granite powder, slag, silica ash, fly ash, sodium silicate solution, sodium hydroxide, basalt fiber, and water. The brick-mud structure composite material is prepared by a paving-type additive and laser subtractive collaborative process, and the specific process is: (1) The platform descends to fix the layer thickness, and the alkali-activated solid waste material that acts as a "brick" is placed in the left material tank and transported to the left extruder through the feed pipe. The left extruder is fixed to the scraper. As the scraper moves from left to right, the alkali-activated solid waste material is extruded onto the workbench. Then, when the extruder and the scraper return to their original positions on the left, the material is evenly spread on the entire work surface through the scraper, and the excess waste is scraped into the waste bin. Since the first layer of material is not tightly bonded to the workbench, it is easy to be carried away when the lower layer of resin is spread after the brick shape is cut, so no other operations are performed on the first layer.

[0023] (2) The workbench is lowered to fix the layer thickness, and the alkali-activated solid waste material is continuously squeezed onto the workbench. It is evenly spread with a scraper, and then the fiber laser is used to cut the plane according to the set path. The laser power and laser speed are adjusted to completely penetrate the layer without cutting into the lower layer, dividing it into pieces of "bricks". After that, it is irradiated with a baking lamp to make the "bricks" of this layer harden quickly and tightly bond with the first layer of slurry, thereby fixing the "bricks" of this layer and facilitating the spreading of the lower layer of resin.

[0024] (3) The workbench is lowered to fix the layer thickness, and the furan resin is placed in the right material tank and transported to the right extruder through the feed pipe. The right extruder is fixed together with the scraper and roller, and the roller can move up and down. During the material spreading process, the roller rises to avoid touching the material on the platform and does not affect the spreading. The spreading process is the same as the spreading of alkali-activated solid waste materials. As the scraper moves to the left, the resin material is squeezed onto the workbench, and as the extruder and the scraper return to their original positions on the right, the material is evenly spread on the entire work surface through the scraper, and the excess waste is scraped into the waste bin. Then, a baking lamp is used to irradiate the resin so that it is heated and solidified. When it solidifies to a certain extent, the roller is started to roll the layer. At this time, the roller on the right moves to the left. When it reaches the workbench, the roller descends to roll the material on the platform, so that the resin material layer and the alkali-activated solid waste material layer are more tightly combined, thereby improving the integrity of the structure and achieving reinforcement and toughening.

[0025] (4) Then, step (2) and step (3) are repeated until printing is completed to obtain a brick-mud structure specimen. In the subsequent repetition of step (2), since the alkali-activated solid waste material and the upper and lower layers of the resin material have a good bonding interface, it can be avoided that after the "brick" is cut, the lower layer has less constraint, which causes the "brick" to be carried away when the subsequent resin material is spread. Each "brick" layer can be laser cut.

[0026] The Mohs hardness of granite is about 6, the density is between 2.63g / cm³ and 2.75g / cm³, the compression strength is 100-300MPa, and the bending strength is 10~30MPa.

[0027] The slag powder has an activity grade of S105 and a density of not less than 1.3 g / cm 3 , of which the CaO content is not less than 40% and the SiO2 content is not less than 25%.

[0028] The SiO2 content of the silica fume powder should not be less than 80%.

[0029] The fly ash powder particle size should be 1250 mesh and the density should be 2.3g / cm 3 , the SiO2 content should not be less than 55%, and the Al2O3 content should not be less than 28%.

[0030] The sodium hydroxide is a solid powder, analytically pure, with a content greater than 96% and a relative molecular mass of 40. The sodium silicate solution is SP38, with a solid content of 35.5, a Baume degree of 38.5, and a density of 1.366 kg / m 3 , the pH value is 10.13 and the modulus is 3.26, which ensures the full dissolution reaction of sodium hydroxide and sodium silicate solution.

[0031] The monofilament diameter of the basalt fiber is 6.23um, the breaking diameter is 1937MPa, the elastic modulus is 79Gpa, the breaking elongation is 2.9, and the preferred basalt fiber length is 1mm to prevent the fiber length from being too long and affecting the paving, and to prevent the alkali-induced solid waste material from shrinking and cracking after being irradiated by a baking lamp.

[0032] The present invention uses a fiber laser to perform brick cutting, and the accuracy can be controlled within 0.01 mm.

[0033] Preferably, the power of the baking lamp used is 1500W, the distance from the workbench is 40cm, the irradiation time for the "brick" layer is 6 minutes, and the "mud" layer is 5 minutes.

[0034] Preferably, the "brick" layer is printed with a thickness of 1 mm.

[0035] Preferably, the laser power is 1000W, the laser energy is 45% and the laser speed is 120mm / s during cutting.

[0036] Preferably, the thickness of the resin material layer is 0.2-0.5 mm, and the rolling depth of the roller is 0.1 mm.

[0037] Example 1 The solid waste-based brick-mud structure composite material of this embodiment includes alkali-activated solid waste material 14 acting as "brick" and thermosetting resin furan resin 13 acting as "mud". The alkali-activated solid waste materials are 80 parts of granite powder, 27.4 parts of slag, 5.2 parts of silica fume, 2 parts of fly ash, 0.41 parts of basalt fiber with a length of 1 mm, 26.3 parts of water, 3.5 parts of sodium hydroxide, and 6.8 parts of sodium silicate solution in parts by weight.

[0038] In this embodiment, the granite powder is ground from the granite in Laizhou, Shandong, has a compressive strength ranging from 100 MPa to 200 MPa, and has good impact resistance. The particle gradation of the granite powder is 100-120 mesh: 200 mesh = 1:1 by weight.

[0039] The preparation process of the composite material is: 1. The preparation process of alkali-activated solid waste materials acting as "bricks" is: (1) Granite powder, slag, silica fume, fly ash and basalt fiber are placed in a mixing pot according to the amount and stirred for 3 minutes to obtain a uniformly mixed dry material.

[0040] (2) Put the obtained dry material and water into a stirring pot and stir them. First, stir them in the forward direction for 5 minutes, and then stir them in the reverse direction for 5 minutes to obtain a uniformly mixed wet material.

[0041] (3) quickly pouring the sodium hydroxide tablets into the beaker containing the sodium silicate solution, and stirring the mixed liquid evenly with a stirring rod. Since a large amount of heat is released when the two materials are mixed, the mixed solution is placed in a refrigerator to cool to room temperature, and finally an alkali activator is obtained.

[0042] (4) The prepared alkali activator and the mixed wet material are placed in a stirring pot and stirred. First, stir in the forward direction for 5 minutes, and then stir in the reverse direction for 5 minutes to obtain a uniformly stirred "brick" alkali-activated solid waste material.

[0043] 2. Paving additive and laser subtractive collaborative process Printing is performed using a 3D printing device, wherein the 3D printing device (see Figure 2 ) is equipped with a heating lamp 7, a fiber laser 9, a scraper 4 and a roller 5, and the heating lamp is 35-45cm away from the workbench 11; a galvanometer 8 is arranged directly above the workbench 11, and the output of the fiber laser 9 acts on the galvanometer 8. Two rows of heating lamps 7 are symmetrically arranged on both sides below the galvanometer 8, and the heating lamps 7 are located above the workbench, and the workbench can be raised and lowered; a waste bin 3 is arranged on both sides of the workbench 11, and a left material tank 1 and a right material tank 2 are arranged outside the waste bin, respectively. The left material tank 1 is used to contain alkali-activated solid waste materials, and the right material pipe is used to contain furan resin; scrapers 4 are arranged on the left and right sides above the workbench, respectively, and the scraper 4 is installed synchronously with the extrusion head 10, and the extrusion head 10 is connected to the material tank on the corresponding side through a feed pipe 6. A roller 5 is also connected to the extrusion head on the side where the furan resin is located, and the roller 5 can be raised and lowered independently; the upper end of the heating lamp is fixed in the machine housing 12.

[0044] (1) The workbench is lowered by 1 mm, and the alkali-activated solid waste material that acts as a "brick" is placed in the material tank on the left. The material is sent to the extruder head 10 through the feed pipe 6. The extruder head and the scraper are fixed together, and the material is extruded onto the workbench while moving to the right with the scraper. Then, when the extruder head and the scraper return to their original positions on the left, the material is evenly spread on the entire work surface through the scraper. No other operations are performed on the first layer.

[0045] (2) The workbench is lowered by 1 mm, and the alkali-excited solid waste material is continuously squeezed onto the workbench. The material is evenly spread by a scraper. The parameters of the fiber laser with a power of 1000 W are set, and the laser energy and laser speed are adjusted to 45% and 120 mm / s, respectively. The fiber laser is used to cut the plane according to the set path. The cutting path is shown in FIG. Figure 3 Then, a 1500W baking lamp was used to irradiate it for 6 minutes at a height of 40cm from the printing platform, so that this layer of "bricks" and the first layer of slurry hardened quickly and bonded tightly, fixing this layer of "bricks" and facilitating the spreading of the lower layer of resin.

[0046] (3) The workbench is lowered by 0.2 mm, and the furan resin is placed in the material tank on the other side, extruded onto the workbench, and evenly spread by a scraper. Then, a 1500 W heating lamp is used to irradiate the furan resin at a height of 40 cm from the printing platform for 5 minutes to heat and solidify the furan resin. When the furan resin solidifies to a certain extent, the right roller is started to roll the layer. The rolling depth of the roller at the workbench is adjustable. In this embodiment, the rolling depth is 0.1 mm. (4) Then continue to repeat steps (2) and (3) until printing is completed to obtain a brick-and-mud structure specimen.

[0047] The printed specimens were cut into 40×40×160mm specimens for flexural testing, and the resulting 28-day flexural strength was 16.1MPa. The 28-day flexural strength of the specimens printed with soda ash-activated solid waste materials in this embodiment was 10.2MPa. Therefore, the effect was significantly improved, and the toughness of the brick-mud structure printed specimens was significantly enhanced.

[0048] The printed specimens were cut into 40×40 mm specimens for compressive strength testing, and the resulting 28-day compressive strength was 43.3 MPa. The 28-day compressive strength of the specimens printed with soda ash-activated solid waste materials in this embodiment was 48 MPa. This shows that the compressive strength of the brick-mud structure specimens in this embodiment is less damaged, with almost no damage.

[0049] Example 2 The paving type additive and laser subtractive collaborative process of this embodiment includes the following steps: (1) The workbench is lowered by 1 mm, and the alkali-activated solid waste material that acts as a "brick" is placed in a material tank, squeezed onto the workbench, and evenly spread on the entire work surface with a scraper. No other operations are performed on the first layer.

[0050] (2) The workbench is lowered by 1 mm, and the alkali-activated solid waste material is continuously squeezed onto the workbench. The material is evenly spread by a scraper, and the parameters of the 1000W fiber laser are set, with the laser energy adjusted to 45% and the laser speed adjusted to 120 mm / s. The fiber laser is used to cut the plane according to the set path, and then a 1500W baking lamp is used to irradiate the plane for 6 minutes at a height of 40 cm from the printing platform, so that the layer of "bricks" and the first layer of slurry are quickly hardened and tightly bonded, which plays a fixing role on the layer of "bricks" and facilitates the spreading of the lower layer of resin.

[0051] (3) The workbench is lowered by 0.4 mm, and the furan resin is placed in the material tank on the other side, extruded onto the workbench, and evenly spread with a scraper. Then, a 1500 W heating lamp is used to irradiate the furan resin at a height of 40 cm from the printing platform for 5 minutes to heat and solidify the furan resin. When the furan resin solidifies to a certain extent, the roller is started to roll the layer with a rolling depth of 0.1 mm. (4) Then continue to repeat steps (2) and (3) until printing is completed to obtain a brick-and-mud structure specimen.

[0052] In this embodiment, the thickness of the resin material layer (before rolling) was changed from 0.2 mm to 0.4 mm, thereby increasing the proportion of resin in the component. The printed specimens were cut into 40×40×160 mm specimens for flexural testing, and the resulting 28-day flexural strength was 18.4 MPa (the flexural strength of soda ash-activated solid waste materials was 10.2 MPa). The effect was significantly improved, and the toughness of the brick-mud structure printed specimens was significantly enhanced.

[0053] The printed specimens were cut into 40×40 mm specimens for compressive strength testing, and the obtained 28-day compressive strength was above 40 MPa. The present invention can maintain a relatively high compressive strength while significantly enhancing the flexural strength.

[0054] Any matters not described in the present invention are applicable to the prior art.

Claims

1. An additive manufacturing method for solid waste-based brick-mud structure composite materials, characterized in that: Using alkali-activated solid waste materials as bricks and thermosetting resin furan resin as mud; The alkali-activated solid waste material comprises, by weight, 80-85 parts of granite powder, 27.4-30 parts of slag, 5-8 parts of silica fume, 1.5-3 parts of fly ash, 0.41-0.43 parts of basalt fiber with a length of 0.8-1.2 mm, 25-27 parts of water, 3.0-3.5 parts of sodium hydroxide, and 6.0-7.0 parts of sodium silicate solution; The weight ratio of the granite powder according to the particle grading is 100-120 mesh: 200 mesh = 1: (1-1.5) The preparation process of the composite material is: 1) placing granite powder, slag, silica ash, fly ash and basalt fiber in a stirring pot and stirring them evenly to obtain a uniformly mixed dry material; placing the mixed dry material and water in a stirring pot and stirring them evenly to obtain a uniformly mixed wet material; quickly pouring sodium hydroxide tablets into a beaker containing sodium silicate solution and stirring them evenly to obtain an alkali activator; Putting the alkali activator and the mixed wet material into a stirring pot and stirring them evenly to obtain the alkali-activated solid waste material; 2) Printing is performed using a 3D printing device, which is equipped with a heating lamp, a fiber laser, a scraper and a roller, and the distance between the heating lamp and the workbench is 35-45 cm; after each layer of alkali-excited solid waste material is printed, the current layer is evenly spread using a scraper, and the fiber laser is used to cut the paved plane according to a set path. Except for the bottom layer, each layer of cutting completely penetrates the current layer, and the current layer is divided into bricks, and then irradiated with a 1500-1600W power heating lamp for 5-6 minutes, so that the current layer quickly hardens and reacts tightly; Furan resin is extruded on the alkali-activated solid waste material layer after being irradiated by a heat lamp, and spread by a scraper. After spreading, it is irradiated by a 1500-1600W power heat lamp for 4-5 minutes to form a resin material layer on the brick layer. When the resin is heated and solidified to a non-sticky roller, the roller is started to roll the layer, so that the resin material layer and the alkali-activated solid waste material layer are organically and tightly combined; The spreading, cutting, baking and rolling processes of the alkali-activated solid waste material and furan resin are repeated until the printing reaches the target height to obtain a brick-mud structure composite material.

2. The manufacturing method according to claim 1, characterized in that: The powder activity grade of the slag is S105, and the density is not less than 1.3g / cm 3 , CaO content is not less than 40%, SiO2 content is not less than 25%; The silica fume has a SiO2 content of not less than 80%; The sodium hydroxide is a solid tablet, analytically pure, with a content greater than 96% and a relative molecular mass of 40. The sodium silicate solution is SP38, with a solid content of 35.5, a Baume degree of 38.5, and a density of 1.366 kg / m 3 , pH value is 10.13, modulus is 3.26; The fly ash powder has a particle size of 1250 mesh and a density of 2.3 g / cm 3 , SiO2 content is not less than 55%, Al2O3 content is not less than 28%; The basalt fiber has a single filament diameter of 6.23 um, a breaking diameter of 1937 MPa, an elastic modulus of 79 Gpa, and a breaking elongation of 2.

9.

3. The manufacturing method according to claim 1, characterized in that: The granite powder is ground from granite in Laizhou, Shandong. The granite compressive strength ranges from 100MPa to 200MPa. The particle grading of the granite powder is 100-120 mesh: 200 mesh = 1:1 in terms of weight ratio.

4. The manufacturing method according to claim 1, characterized in that: The power of the baking lamp is 1500W, the distance from the workbench is 40cm, the irradiation time for the brick layer is 6 minutes, and the irradiation time for the mud layer is 5 minutes.

5. The manufacturing method according to claim 1, characterized in that: The thickness of the resin material layer is 0.2-0.5mm, the rolling depth of the roller is 0.1mm, and the rolling depth is the depth of the roller into the paving layer; the thickness of the brick layer printing layer is 1mm.

6. The manufacturing method according to claim 1, characterized in that: The laser power of the fiber laser is 1000W, the laser energy during cutting is 45%, and the laser speed is 120mm / s.

7. A solid waste-based brick-mud structural composite material obtained by the manufacturing method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • 3DP synchronous micro-rolling printing method, application and printer

    CN116330645A

  • Additive 3D manufacturing using light-cured resin

    WO2024184876A1

  • Additive manufacturing method and device for complex structure of fiber reinforced composite material

    WO2024221516A1